2015
DOI: 10.20396/san.v17i1.8634801
|View full text |Cite
|
Sign up to set email alerts
|

Condições socioeconômicas, demográficas e estado nutricional de adultos e idosos moradores em assentamento rural em Mato Grosso do Sul, MS.

Abstract: O objetivo deste trabalho foi avaliar as condições socioeconômicas, demográficas e o estado nutricional de adultos e idosos, moradores em assentamento rural, Ponta Porã, Mato Grosso do Sul (Brasil). Participaram da amostra indivíduos com idade entre 20 e 69 anos. Integraram a pesquisa 117 unidades domiciliares, envolvendo 217 pessoas (105 do gênero feminino e 112 do masculino). Verificou-se que a maioria dos entrevistados era casada e apresentaram média de 43 anos de idade e 5,2 anos de estudo. Entre as assent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
2
1
6
Order By: Relevance
“…Some studies have already identified a relation between food insecurity and overweight, since it has increased in the economically disadvantaged classes, probably due to the acquisition of foods with low nutritional value and high caloric density at lower prices 9,25,26 . In contrast to other studies 9,[27][28][29][30] , schooling showed no association with FNI, probably because this population is very homogeneous regarding low schooling, a result also found in other settled populations 7,21,31 . Low schooling contributes to people generally not getting well paid work opportunities outside the settlements, not promoting increased income and decreased food insecurity.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have already identified a relation between food insecurity and overweight, since it has increased in the economically disadvantaged classes, probably due to the acquisition of foods with low nutritional value and high caloric density at lower prices 9,25,26 . In contrast to other studies 9,[27][28][29][30] , schooling showed no association with FNI, probably because this population is very homogeneous regarding low schooling, a result also found in other settled populations 7,21,31 . Low schooling contributes to people generally not getting well paid work opportunities outside the settlements, not promoting increased income and decreased food insecurity.…”
Section: Discussioncontrasting
confidence: 99%
“…Os assentados pesquisados possuem idade inferior aos dados demonstrados no trabalho desenvolvido por Bergamasco (1997), que apontou que 48,4% do total dos titulares dos lotes de assentamentos, no Brasil, possuí entre 36 e 57 anos, enquanto Fietz et al (2010) em estudo em assentamento em Mato Grosso do Sul registraram a idade média de 43 anos.…”
Section: Resultsunclassified
“…Other studies that assessed the nutritional status of rural populations observed a frequency of excess weight of 45.5% in the state of Mato Grosso do Sul 18 and 40.7% in rural communities in the state of Sergipe 19 . High frequency of excess weight plays a significant role as it poses risks for developing cardiovascular diseases, the main cause of mortality worldwide 20 .…”
Section: Discussionmentioning
confidence: 96%